Rethinking the Limits of Endemic Cannibalism: on Cinco Voltas na Bahia e um Beijo para Caetano Veloso - Correa de Sa, Andre (Nau Literária, 2025)
This paper undertakes the unconventional experiment of arguing that the metaphor of anthropophagy is oversimplified and readily deployed, often without critical examination. Through a reading of Alexandra Lucas Coelho’s 2019 non-fiction book, Cinco Voltas na Bahia e um Beijo para Caetano Veloso, I argue that the concept of cultural cannibalism as a progressive and transformative force is shaped by Brazilian self-representations that frequently obscure the complex historical and cultural tensions inherent in it, making it not unlike other forms of exceptionalism. By idealizing Antropofagia as a decolonial critical method, Lucas Coelho inadvertently reinforces how the notion of cultural cannibalism has been appropriated by hegemonic structures to perpetuate national unity narratives that gloss over persistent inequalities. Moreover, Lucas Coelho’s interpretation leans on an exoticist aesthetic, reducing Brazil’s cultural complexities to a consumable, exportable spectacle. This paper, therefore, challenges the foundational promises of cultural cannibalism, exploring how its celebrated triumph not only obscures unequal power relations but also streamlines the intricate interplay of hegemony, exoticism, and cultural production in Brazil’s political and cultural history.